The unseen world: environmental microbial sequencing and identification methods for ecologists. Issue 4 (1st May 2014) - Zimmerman, Naupaka; Izard, Jacques; Klatt, Christian; Zhou, Jizhong; Aronson, Emma
Abstract : Microorganisms inhabit almost every environment, comprise the majority of diversity on Earth, are important in biogeochemical cycling, and may be vital to ecosystem responses to large‐scale climatic change. In recent years, ecologists have begun to use rapidly advancing molecular techniques to address questions about microbial diversity, biogeography, and responses to environmental change. Studies of microbes in the environment generally focus on three broad objectives: determining which organisms are present, what their functional capabilities are, and which are active at any given time. However, comprehending the range of methodologies currently in use can be daunting. To provide an overview of environmental microbial sequence data collection and analysis approaches, we include case studies of microbiomes ranging from the human mouth to geothermal springs. We also suggest contexts in which each technique can be applied and highlight insights that result from their use.